STATE LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION ORAL LIQUID OF PATIENTS WITH HIV STATUS - Іленко, Н.В.; Петрушанко, Т.О.; Іленко, Н.М. (World of Medicine and Biology, 2015)
In this article it was shown the results of our research. We studied the intensity of free radical processes (FRP) and the activity of antioxidant systems (AOS) in oral liquid of HIV-patients. It was found that the rates of catalase and SOD activity of salivary glands in HIV-patients were significantly higher compared with those indexes in the control group. This changes were caused by prolonged stress, high emotional stress and depressive state of patients with HIV status. Studying the initial level of TBA-active products and growth in their concentration in the oral liquid of research group showed significantly higher levels of value compared to the representatives of the control group. It was also found that the intensity of free radical processes and activity of antioxidant systems increases with the progression of immunodeficiency and with the progression of periodontal diseases.
Keywords: HIV infection; oral liquid; periodontal diseases; lipid peroxidation; antioxidant system